(untitled) (The Journal of Building and Land Development, 2020)
This study aimed at investigating occurrence and levels of indicator pathogenic microorganisms from traditional open markets (TOM) dealing with selling and slaughtering of live avian. Manzese and Buguruni TOM both in Dar es Salaam were selected as case study areas. The field survey revealed that the TOM receive over 60,000 avian per month from all regions of Tanzania and neighbouring countries out of which 52% are free-range kept indigenous chicken. Using biochemical test and a selective media, three Enterobacteria (E. coli, Klebsiella pneumonia and Salmonella) were identified and quantified following bacteriological analysis of soil, leachate and biowaste samples collected from both TOM. All samples showed high enterobacteria load >log1.0CFU/g. Leachate (pH 7.4) fromManzese TOM showed significant increase (p<0.05) inE. coli and Salmonella population up to 7.6Â±1.1logCFU/mL and 5.7Â±2.1logCFU/mL, respectively. High level of E. coli and Salmonella in all samples indicate the possibility of many other potentially pathogenic micro organisms while the observed unsatisfactory handling of avian droppings, blood and post-processing remains, confirmed the threat of human exposure to potentially pathogenic microorganisms at TOM. In this study, a range of recommendations to prevent human exposure to disease-causing agents at TOM and possibly elsewhere are presented. Keywords: Traditional Open Market, Avian, Enterobacteria, Epidemics, Dar es Salaam